2013
DOI: 10.1103/physreva.88.043845
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion cancellation in high-resolution two-photon interference

Abstract: The dispersion cancellation observed in Hong-Ou-Mandel (HOM) interference between frequency-entangled photon pairs has been the basis of quantum optical coherence tomography and quantum clock synchronization. Here we explore the effect of phase dispersion on ultranarrow HOM dips. We show that the higher-order dispersion, the linewidth of the pump laser, and the spectral shape of the parametric fluorescence have a strong effect on the dispersion cancellation in the high-resolution regime with several experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…4d ) calculated taking the higher-order dispersion of the 1 mm thickness of water 38 into account fits also well with the experimental data. Note that the asymmetricity of the HOM dip observed in the experimental data is due to the higher odd-order dispersion 28 39 , which can be also observed in the theoretical curve. Our theoretical calculation suggests that the resolution will be still kept 0.60 μ m even when a thickness of water is increased to 3 mm.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…4d ) calculated taking the higher-order dispersion of the 1 mm thickness of water 38 into account fits also well with the experimental data. Note that the asymmetricity of the HOM dip observed in the experimental data is due to the higher odd-order dispersion 28 39 , which can be also observed in the theoretical curve. Our theoretical calculation suggests that the resolution will be still kept 0.60 μ m even when a thickness of water is increased to 3 mm.…”
Section: Resultssupporting
confidence: 65%
“…3a upper inset). The temperature T is controlled by a thermoelectric cooler with an accuracy of 0.1 K. We have found that in ultra-high resolution regime the linewidth of a pump laser degrades the dispersion tolerance 28 . To ensure the dispersion tolerance, we used a narrowband pump laser (~100 kHz) with a wavelength of 401 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of its relevance for quantum technology [9,13], * Electronic address: zeudi.mazzotta@unimi.it † Electronic address: simone.cialdi@unimi.it ‡ Electronic address: daniele.cipriani@mi.infn.it § Electronic address: stefano.olivares@fisica.unimi.it ¶ Electronic address: matteo.paris@fisica.unimi.it theoretical [14][15][16] and experimental [17][18][19][20] studies have been performed to characterize TPI and the HOM dip. However, a full analysis of both the visibility and the width of the HOM dip as a function of the pump spectrum and of the PDC spectrum is still missing.…”
Section: Introductionmentioning
confidence: 99%